Frosted reinforcing glue and preparation method thereof
By using specific thiol modified polyurethane acrylate and aliphatic difunctional agglomerated polyurethane acrylate, the prepared frosted reinforced glue solves the problems of poor recoating and low connection strength of the insulation layer in the existing UV curing nail art process, achieving a comprehensive effect of high mechanical strength, quick dryness and low calorie, and improving the experience of nail art.
Patent Information
- Application Number
- CN202411841338.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing UV curing nail art process, the adhesive glue of the isolation layer has poor recoating properties, low connection strength, easy to fall off, and it is difficult to take into account the characteristics of quick dryness and low heat.
A matte reinforcement glue is prepared using specific thiol modified polyurethane acrylate and aliphatic difunctional agglomerated polyurethane acrylate as key ingredients. This product is used in the isolation layer and has excellent curing resistance to oxidation and polymerization, reducing adhesion effect, improving the recoating ability of the adhesive powder glue, and improving the binding force with other manicure layers.
It has effectively combined color glue and sealing glue in the nail art process, and has strong recoating properties on the surface of the adhesive powder glue, almost non-stick magic mirror powder, high mechanical strength, not easy to be damaged, fast drying rate, and low heat release in curing, which improves the user experience.
Smart Images

Figure BDA0005188036050000141 
Figure BDA0005188036050000151 
Figure BDA0005188036050000171
Abstract
Description
Technical Field
[0001] The invention relates to the field of nail art, and in particular to a frosted reinforcing glue and a preparation method thereof. Background Art
[0002] With the accelerated pace of life, many nail art enthusiasts no longer have enough time to go to nail salons for traditional manicures. Therefore, the early self-drying nail glue has been basically eliminated. In response to the needs of the market, UV-curing (ultraviolet light-curing) nail glue with fast curing characteristics has emerged. This product only needs to be exposed to a UV nail lamp for a few seconds to achieve curing, and its convenience is now improved.
[0003] The general steps of the current mainstream UV curing manicure process are: apply base glue to nails, cure, apply color glue on the base glue, cure, apply an isolation layer on the color glue, cure, apply sticky powder glue on part of the isolation layer, cure, apply magic mirror powder to the area with sticky powder glue, remove excess magic mirror powder, apply a sealing layer on the sticky powder layer and the area without sticky powder glue, cure, and stick the outermost layer of decoration. The isolation layer in this process is generally a matte sealing glue, but this material has many defects: (1) The recoatability of the powder adhesive on its surface is poor; (2) The connection strength with the color glue and the subsequent brush-coated sealing glue is low and it is very easy to fall off; (3) The adsorption capacity for magic mirror powder is relatively high. Since the main function of the isolation layer is to isolate excess magic mirror powder to prevent it from falling on the nails or nail plates and affecting the appearance, but due to the properties of the UV matte sealing glue, the magic mirror powder applied outside the powder adhesive area is difficult to remove; (4) The mechanical strength is insufficient and it is difficult to play a certain reinforcement role. As a result, if the isolation layer is damaged after being subjected to a certain external force, the product may directly delaminate or even fall off.
[0004] On the other hand, the UV curing manicure process involves a lot of curing steps. When curing the UV matte sealant layer, some fast-drying products tend to emit high heat in a short time, causing a burning sensation on the nails of the manicurist. In order to solve this problem, people currently use some free radical curing system products as a substitute. However, since the power of most current UV nail lamps is very low, in actual application, the curing time is significantly increased compared to fast-drying products. Summary of the invention
[0005] Based on the defects of the prior art, the purpose of the present invention is to provide a frosted reinforcing glue, which creatively solves the dilemma of the lack of special isolation layer products in the existing popular nail art process. It can not only effectively combine color glue and sealing glue in the nail art process, but also has strong recoatability on the surface of powder glue and can almost achieve non-stick magic mirror powder. The product has high mechanical strength, is not easily damaged, has a fast surface drying rate, and releases low heat during curing. As an intermediate connecting layer of nail art, it can be thickly coated and reinforced multiple times to enhance the user experience.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A frosted reinforcing adhesive comprises the following components in parts by weight:
[0008] 10-40 parts of mercaptan-modified polyurethane acrylate, 20-40 parts of aliphatic difunctional polyurethane acrylate;
[0009] The thiol-modified polyurethane acrylate comprises the following preparation raw materials:
[0010] HDI (hexamethylene diisocyanate), polycaprolactone diol, polyethylene glycol, pentaerythritol tetrakis(3-mercaptopropionic acid) ester, pentaerythritol triallyl ether and 3-mercapto-1-propanol;
[0011] The aliphatic difunctional polyurethane acrylate comprises the following preparation raw materials:
[0012] IPDI (isophorone diisocyanate), polyether diol, HEA (hydroxyethyl acrylate); the molecular weight of the polyether diol is ≥3000.
[0013] In the existing nail art process, the isolation layer glue used between the color glue and the sealing glue is generally a matte sealing glue, but this type of product is difficult to achieve the expected interlayer bonding strength and is very easy to stick to powder, resulting in unclear contours of the pattern effect created by using magic mirror powder and sticky powder glue, and the recoatability of the sticky powder glue is also poor. Therefore, in the scheme described in the present invention, after research, the inventors use two specific polyurethane acrylates as key ingredients to prepare a frosted reinforcement glue specifically used in the above-mentioned scenario. When this product is used as an isolation layer, the thiol-modified polyurethane acrylate with a specific functional group can show excellent curing antioxidant inhibition, and its adhesion effect after curing is greatly reduced, and the adhesion of the product is The probability of powder is greatly reduced, and the recoatability of the adhesive is improved; the aliphatic difunctional polyurethane acrylate uses IPDI and HEA as hard segments and polyether diol as soft segments. This composite chain component can not only effectively improve the hardness and flexibility of the product, but also effectively enhance its bonding with other nail layers in combination with thiol modification; on the other hand, after compounding, the two special polyurethane acrylates can not only achieve good fast surface drying properties and improve the speed of the nail process, but also the overall resin emits very low heat during curing, and the user will hardly feel heat during the gluing process, which effectively solves the dilemma that existing UV-curing isolation layers cannot have both fast drying and low heat generation.
[0014] In the frosted reinforcing glue described in the present invention, the synergistic effect of the two polyurethane acrylates is mainly due to the specific functional group combination and molecular chain structure of the two. If the types of raw materials are not appropriate in the preparation process, it is difficult to prepare a resin component with the same structural composition, and the combination of the two cannot achieve the expected effect, especially in the aliphatic difunctional polyurethane acrylate, the polyether diol used as the preparation raw material needs to reach a sufficient molecular weight to ensure that the aliphatic difunctional polyurethane acrylate has sufficient resistance, hardness and flexibility, so as to adapt to the function of the frosted reinforcing glue; at the same time, the combination amount of the two polyurethane acrylates described in the present invention has a great influence. An imbalance in the addition amount of any one of them will result in the product being unable to take into account the comprehensive effects of interlayer bonding, non-stick powder effect, mechanical properties, quick drying and low heat, and may even result in the serious consequence that the product cannot be used at all. Therefore, it is necessary to strictly limit the ratio of the two resins.
[0015] It should be noted that the molecular weight of the polyether diol is an average molecular weight.
[0016] Preferably, the components of the frosted reinforcing adhesive further include 10 to 20 parts of matte polyurethane acrylate and 2 to 10 parts of matte powder.
[0017] The main reason why matte-series sealing glue is selected as the isolation layer in the existing nail art process is that general powder adhesives are colorless and transparent, and if a glossy isolation layer is used for matching, it is difficult to distinguish the outline of the powder adhesive, which is not conducive to pattern depiction. In order to achieve product compatibility, the present invention additionally introduces a third matte-series polyurethane acrylate as a matting component in the two specific polyurethane acrylate components to ensure the convenience and accuracy of pattern depiction, and further introduces a certain amount of matting powder to improve the distinction of the pattern depiction outline. However, the amount of matting powder introduced needs to be appropriate, because the matting powder will affect the viscosity and thixotropy of the product. If too much is introduced, or matte polyurethane acrylate is not introduced at all, and only matting powder is introduced to reduce the gloss of the product, the appearance effect may be deteriorated due to the viscosity and thixotropy of the product. After screening, the combination of matte polyurethane acrylate and matting powder in the above-mentioned ratio is the best.
[0018] It should be noted that the present invention has no additional restrictions on the type and structure of the matte polyurethane acrylate. It can be a commercially available product or a homemade product with a matte effect. Its main function is to give the product a matte color without affecting the synergistic effect of the other two specific polyurethane acrylates. Any product that meets this condition can be used.
[0019] More preferably, the matte polyurethane acrylate is at least one of Baojun Chemical's 2022 product, Haohui New Materials' CR92209 product, and Wuxing New Materials' LED9505 product.
[0020] Preferably, the matting powder is modified fumed silica.
[0021] More preferably, the modified fumed silica is polydimethylsiloxane-modified fumed silica.
[0022] Fumed silica has the characteristics of fine particles and good light refraction effect, but if it is directly introduced into the frosted reinforcing glue described in the present invention, it may cause incompatibility or uneven dispersion of particles. Therefore, polydimethylsiloxane modification can introduce an appropriate amount of active groups on its surface, making the matting powder more compatible.
[0023] More preferably, among the components of the frosted reinforcing glue, the weight proportion of thiol-modified polyurethane acrylate is in the range of 10 parts, 15 parts, 20 parts, 30 parts, 35 parts, 40 parts or any two of them, the weight proportion of aliphatic difunctional polyurethane acrylate is in the range of 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or any two of them, the weight proportion of matte polyurethane acrylate is in the range of 10 parts, 12 parts, 15 parts, 18 parts, 20 parts or any two of them, and the weight proportion of matting powder is in the range of 2 parts, 5 parts, 8 parts, 10 parts or any two of them.
[0024] More preferably, the frosted reinforcing adhesive comprises the following components in parts by weight:
[0025] 30-40 parts of mercaptan-modified polyurethane acrylate, 20-30 parts of aliphatic difunctional polyurethane acrylate;
[0026] Preferably, in the raw materials for preparing the thiol-modified polyurethane acrylate, the molecular weight of the polycaprolactone diol is 300-1800.
[0027] More preferably, in the raw materials for preparing the thiol-modified polyurethane acrylate, the molecular weight of the polycaprolactone diol is 400-1500.
[0028] More preferably, in the raw materials for preparing the thiol-modified polyurethane acrylate, the molecular weight of the polycaprolactone diol is 800-900.
[0029] Preferably, in the raw material for preparing the thiol-modified polyurethane acrylate, the molecular weight of polyethylene glycol is 100-2200.
[0030] More preferably, in the raw materials for preparing the thiol-modified polyurethane acrylate, the molecular weight of polyethylene glycol is 200-2000.
[0031] More preferably, in the raw material for preparing the thiol-modified polyurethane acrylate, the molecular weight of polyethylene glycol is 750-850.
[0032] The molecular weights of the polycaprolactone diol and polyethylene glycol mentioned above are average molecular weights.
[0033] When preparing mercaptan-modified polyurethane acrylate, the selection of polycaprolactone diol and polyethylene glycol needs to fully consider their reactivity during the reaction and the molecular weight of the obtained product. If the molecular weight of the two is too large, the reactivity of the product will be reduced. If the molecular weight is small, not only the activity of the material will be reduced during the reaction, but also the mercaptan-modified polyurethane acrylate will release too much heat during curing, and the flexibility will be reduced, which directly affects the performance. After optimization, when the molecular weight of the two raw materials is selected within the above range, the product can achieve the best use effect.
[0034] More preferably, the thiol-modified polyurethane acrylate comprises the following raw materials in parts by weight:
[0035] 15-20 parts of HDI, 10-40 parts of polycaprolactone diol, 5-50 parts of polyethylene glycol, 32-49 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0-15 parts of pentaerythritol triallyl ether, 0.1-1 parts of 3-mercapto-1-propanol, 0.01-0.5 parts of inhibitor, 0.01-0.5 parts of stabilizer and 0.01-0.5 parts of catalyst;
[0036] More preferably, the thiol-modified polyurethane acrylate comprises the following raw materials in parts by weight:
[0037] 15-20 parts of HDI, 15-25 parts of polycaprolactone diol, 15-25 parts of polyethylene glycol, 32-49 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0-15 parts of pentaerythritol triallyl ether, 0.1-1 parts of 3-mercapto-1-propanol, 0.01-0.5 parts of inhibitor, 0.01-0.5 parts of stabilizer and 0.01-0.5 parts of catalyst;
[0038] More preferably, the thiol-modified polyurethane acrylate comprises the following raw materials in parts by weight:
[0039] 16-17 parts of HDI, 16-21 parts of polycaprolactone diol, 20-24 parts of polyethylene glycol, 40-49 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0-9 parts of pentaerythritol triallyl ether, 0.4-0.6 parts of 3-mercapto-1-propanol, 0.08-0.12 parts of polymerization inhibitor, 0.2-0.3 parts of stabilizer and 0.2-0.4 parts of catalyst;
[0040] With the difference in the selection ratio of the raw materials for preparation, the molecular structure and the degree of thiol modification of the thiol-modified polyurethane acrylate are different, and finally the antioxidant inhibition ability and mechanical properties thereof are different. It is found through experiments that when the raw materials within the above-mentioned preferred ratio range are selected to react and prepare the thiol-modified polyurethane acrylate, the comprehensive performance of the product is the best.
[0041] More preferably, the inhibitor is at least one of hydroquinone (HQ), p-hydroxyanisole (MEHQ), and N-nitroso-N-phenylhydroxylamine aluminum (510); the stabilizer is at least one of TP-10P of Double Bond Chemical and G20 of Ruian Company; and the catalyst is at least one of dibutyltin dilaurate (DBT), bismuth laurate, and triethylamine.
[0042] More preferably, the method for preparing the thiol-modified polyurethane acrylate comprises the following steps:
[0043] (1) mixing HDI, polycaprolactone diol, polyethylene glycol and the first part of the catalyst and heating to 65-75° C. to react until the NCO content in the obtained mixture reaches the theoretical value, and cooling to room temperature;
[0044] (2) adding pentaerythritol tetrakis(3-mercaptopropionic acid), an inhibitor and a second part of the catalyst to the mixture, mixing and heating to 58-62° C. for reaction for 0.8-1.2 hours, then heating to 68-72° C. and adding pentaerythritol triallyl ether, 3-mercapto-1-propanol, a stabilizer and the remaining catalyst to mix and react until the NCO content in the mixture is 0%, thereby obtaining the thiol-modified polyurethane acrylate.
[0045] It should be noted that the preparation method of the thiol-modified polyurethane acrylate of the present invention is not limited thereto, and those skilled in the art can prepare products using the above-mentioned preparation raw materials by other reaction processes or reaction instruments according to actual needs, as long as the product can achieve the expected effect of the thiol-modified polyurethane acrylate of the present invention.
[0046] At the same time, the theoretical value corresponding to the NCO content in step (1) is calculated by those skilled in the art based on the molecular weights of polycaprolactone diol and polyethylene glycol. The theoretical values of raw materials with different molecular weights are different. For example, in the technical solution of the present invention, some theoretical values can be 7 to 10%.
[0047] Preferably, in the raw material for preparing the aliphatic difunctional polyurethane acrylate, the molecular weight of the polyether diol is 3000-5000.
[0048] More preferably, in the raw material for preparing the aliphatic difunctional polyurethane acrylate, the molecular weight of the polyether diol is 3000-3200.
[0049] As mentioned above, the selection of polyether diol will directly affect the curing performance, flexibility and powder adhesion of the prepared aliphatic difunctional polyurethane acrylate and thiol-modified polyurethane acrylate. If the molecular weight is too small, the product performance will not meet expectations, but if the molecular weight is too large, the viscosity of the product will increase excessively, resulting in low product stability. Therefore, the use of polyether diols within the above preferred range is the best.
[0050] More preferably, the aliphatic difunctional polyurethane acrylate comprises the following raw materials in parts by weight:
[0051] 20-30 parts of IPDI, 130-170 parts of polyether diol, 20-30 parts of HEA, 0.01-1 parts of inhibitor and 0.01-1 parts of catalyst;
[0052] More preferably, the aliphatic difunctional polyurethane acrylate comprises the following raw materials in parts by weight:
[0053] IPDI 22-23 parts, polyether diol 145-155 parts, HEA 22-25 parts, inhibitor 0.08-0.12 parts and catalyst 0.1-0.3 parts;
[0054] More preferably, the catalyst is at least one of dibutyltin dilaurate (DBT) and bismuth laurate, and the inhibitor is at least one of hydroquinone (HQ), p-hydroxyanisole (MEHQ), and N-nitroso-N-phenylhydroxylamine aluminum (510).
[0055] In the prior art, there are many types of aliphatic polyurethane acrylates that can be used for UV curing. However, due to differences in molecular structure and functional group types, the curing effect during curing and the mechanical strength after curing are also different. In particular, during curing, due to structural differences, the heat release efficiency varies greatly. When using the thiol-modified polyurethane acrylate described in the present invention, if a synergistic effect is to be achieved, the selection of hard segments and soft segments is particularly critical, and the ratio of the two molecular segments needs to be considered. The inventors have found through experiments that when the raw materials in the above ratio are selected to prepare the product, the best comprehensive performance is achieved.
[0056] More preferably, the method for preparing the aliphatic difunctional polyurethane acrylate comprises the following steps:
[0057] (1) mixing IPDI, polyether diol and the first part of the catalyst and heating to 75-85° C. under a protective atmosphere to react until the NCO content in the obtained mixture reaches the theoretical value, and then cooling to 35-45° C.;
[0058] (2) HEA and the remaining catalyst are added to the mixture and mixed, and then an inhibitor is added and the reaction is continued until the NCO content in the mixture is 0%, thereby obtaining the aliphatic difunctional polyurethane acrylate.
[0059] It should be noted that the preparation method of the aliphatic difunctional polyurethane acrylate described in the present invention is not limited thereto, and those skilled in the art can prepare aliphatic difunctional polyurethane acrylates of the same configuration from hard segment raw materials and soft segment raw materials according to other processing techniques or processing sequences based on actual needs and the synthesis path rules of conventional aliphatic polyurethane acrylates, as long as the product can achieve the expected technical effect.
[0060] As above, different theoretical values of NCO content of the mixture can be calculated for polyether diols with different molecular weights. For example, in some embodiments of the present invention, the theoretical value can be 2 to 2.5%.
[0061] Preferably, the frosted reinforcing glue also includes 5 to 20 parts of acrylate monomer;
[0062] More preferably, the acrylic acid ester monomer is at least one of hydroxyethyl acrylate, isobornyl acrylate, and methacrylate.
[0063] In order to enhance the bonding effect of the two specific polyurethane acrylates of the present invention, acrylate monomers are required to cross-link them with each other, and the above-mentioned acrylate monomers can well play a role in cross-linking and neutralizing each component, thereby improving the performance stability of the product.
[0064] Preferably, the components of the frosted reinforcement glue also include 1 to 6 parts of photoinitiator, 0.1 to 1 part of defoamer, 0.1 to 1 part of dispersant and 0.1 to 1 part of leveling agent.
[0065] More preferably, the photoinitiator is a TPO initiator.
[0066] More preferably, the defoaming agent is a non-silicone defoaming agent.
[0067] The inventors have found through experiments that since the product described in the present invention is an isolation layer, it is necessary to focus on the combination effect of the corresponding powder adhesive and sealing adhesive. If a silicone defoamer is used, the recoating effect of the powder adhesive may be reduced. Therefore, the comprehensive effect of selecting a non-silicone defoamer is the best.
[0068] More preferably, the dispersant is a modified silicone dispersant.
[0069] More preferably, the dispersant is at least one of TEGO 689, BYK 2008 and BYK 2009.
[0070] More preferably, the leveling agent is a polyacrylate leveling agent.
[0071] It should be noted that the components of the frosted reinforcing glue of the present invention may also include other types. For example, in order to improve the antioxidant performance of the product, those skilled in the art may introduce 0.1 to 1 parts of antioxidants according to actual needs. The antioxidants may be commercially available hindered phenols or phosphite antioxidants. Similarly, in order to improve the appearance of the product, those skilled in the art may introduce 0.1 to 1 parts of colorants according to actual needs. The selection of the product components described in the present invention is not a limitation on the product components.
[0072] Another object of the present invention is to provide a method for preparing the frosted reinforcing adhesive, comprising the following steps:
[0073] (1) mixing thiol-modified polyurethane acrylate, aliphatic difunctional polyurethane acrylate, matte polyurethane acrylate, acrylate monomer and photoinitiator until uniform to obtain a mixture A;
[0074] (2) adding matting powder, defoaming agent, dispersant and leveling agent to mixture A and continuing to mix until uniform, to obtain mixture B;
[0075] (3) The mixture is passed through a 100-200 mesh sieve to obtain the frosted reinforcing adhesive.
[0076] Preferably, the mixing rate in step (1) is 750-1000 rpm, and the mixing time is 10-15 min;
[0077] Preferably, the mixing rate in step (2) is 1200-1500 rpm, and the mixing time is 20-30 min.
[0078] The preparation method of the frosted reinforcing glue of the present invention has simple operation steps and does not require special equipment processing. Technical personnel in the field can prepare it in a conventional factory, and can even prepare the components into products in real time according to the actual requirements of the products before manicure and directly apply them, which has strong operational flexibility.
[0079] Another object of the present invention is to provide an application of the frosted reinforcing glue as an isolation layer in a nail art process.
[0080] Another object of the present invention is to provide a manicure comprising the abrasive reinforcing glue of the present invention.
[0081] As described above, the frosted processing glue of the present invention can completely replace the traditional UV-curing resin in the existing nail art process and be used as a special isolation layer resin. This product can not only effectively combine with powder sticking glue and sealing glue, but also significantly improve the recoating performance of powder sticking glue, and will not cause powder sticking. At the same time, it exhibits good mechanical properties and performance, and the curing process time is short and the heat dissipation is low.
[0082] The beneficial effects of the present invention are as follows: the present invention discloses a frosted reinforcement glue, which creatively solves the dilemma of no special isolation layer products in the existing popular nail art process, and can not only effectively combine color glue and sealing glue in the nail art process, but also has strong recoatability on the surface of sticky powder glue, and can almost achieve non-stick magic mirror powder; the product has high mechanical strength, is not easy to be damaged, has a fast surface drying rate, and releases low heat during curing. As a middle connecting layer of nail art, it can be thickly coated and reinforced multiple times, thereby improving the user experience. The present invention also discloses the application of the frosted reinforcement glue as an isolation layer in the nail art process. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 The nail piece is used when the frosted reinforcement glue of the present invention is subjected to a powder-free test.
[0084] Figure 2 It is a schematic diagram of a sample of the frosted reinforcement adhesive of the present invention after being coated with powder sticking adhesive during a powder-free test.
[0085] Figure 3 Schematic diagram of a nail plate sample prepared with the frosted reinforcing glue described in the present invention. DETAILED DESCRIPTION
[0086] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents, raw materials and instruments designed for the implementation of the present invention and comparative examples are all commonly used ordinary reagents, raw materials and instruments unless otherwise specified.
[0087] It should be noted that the terms "include", "comprises" and "have" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or units that are inherent to these processes, methods, products or devices. In the claims, specifications and drawings of the present invention, relational terms such as "first" and "secondly" are merely used to distinguish one entity / operation / object from another entity / operation / object, and do not necessarily require or imply any such actual relationship or order between these entities / operations / objects.
[0088] In the present invention, a frosted reinforcing adhesive comprises the following components in parts by weight:
[0089] 10-40 parts of mercaptan-modified polyurethane acrylate, 20-40 parts of aliphatic difunctional polyurethane acrylate;
[0090] Furthermore, in some embodiments, the components also include 10 to 20 parts of matte polyurethane acrylate, 2 to 10 parts of matting powder, 5 to 20 parts of acrylate monomer, 1 to 6 parts of photoinitiator, 0.1 to 1 part of defoaming agent, 0.1 to 1 part of dispersant and 0.1 to 1 part of leveling agent.
[0091] In a specific embodiment of the present invention, the method for preparing the frosted reinforcing adhesive comprises the following steps:
[0092] (1) mixing thiol-modified polyurethane acrylate, aliphatic difunctional polyurethane acrylate, matte polyurethane acrylate, acrylate monomer and photoinitiator until uniform to obtain a mixture A;
[0093] (2) adding matting powder, defoaming agent, dispersant and leveling agent to mixture A and continuing to mix until uniform, to obtain mixture B;
[0094] (3) Pass the mixture through a 100-mesh sieve to obtain the frosted reinforcing glue.
[0095] Furthermore, in step (1), the mixing rate is 800 rpm and the mixing time is 12 min;
[0096] Furthermore, in the step (2), the mixing rate is 1400 rpm and the mixing time is 25 min.
[0097] In some embodiments, the thiol-modified polyurethane acrylate comprises the following raw materials in parts by weight:
[0098] 15-20 parts of HDI, 17-25 parts of polycaprolactone diol, 15-25 parts of polyethylene glycol, 32-49 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0-15 parts of pentaerythritol triallyl ether, 0.1-1 parts of 3-mercapto-1-propanol, 0.01-0.5 parts of inhibitor, 0.01-0.5 parts of stabilizer and 0.01-0.5 parts of catalyst;
[0099] The HDI is hexamethylene diisocyanate (HDI) produced by Bayer;
[0100] The molecular weight of the polycaprolactone diol 1 is 830, and it is a 2083 model produced by Hunan Juren New Materials Company; the molecular weight of the polycaprolactone diol 2 is 400, and it is a 2044 model produced by Hunan Juren New Materials Company; the molecular weight of the polycaprolactone diol 3 is 1500, and it is a 2151 model produced by Hunan Juren New Materials Company;
[0101] The tetrakis(3-mercaptopropionic acid) pentaerythritol ester is produced by Qingdao Zhongke Huatai Chemical Co., Ltd.
[0102] The pentaerythritol triallyl ether is pentaerythritol triallyl ether produced by Zhongshan Dixin Chemical Company;
[0103] The molecular weight of the polyethylene glycol 1 is 800, which is PEG-800 produced by Jiangsu Haian Petrochemical Company; the molecular weight of the polyethylene glycol 2 is 200, which is PEG-200 produced by Jiangsu Haian Petrochemical Company; the molecular weight of the polyethylene glycol 3 is 2000, which is PEG-2000 produced by Jiangsu Haian Petrochemical Company;
[0104] The 3-mercapto-1-propanol is 3-mercapto-1-propanol produced by Sanmenxia Aoke Chemical Co., Ltd.
[0105] The inhibitor is methyl parahydroxyanisole (MEHQ) produced by Solvay Chemical Company;
[0106] The stabilizer is TP-10H produced by Double Bond Chemical;
[0107] The catalyst is dibutyltin dilaurate (DBT) produced by Shandong Yuanjin New Materials Co., Ltd.
[0108] In some embodiments, the method for preparing the thiol-modified polyurethane acrylate comprises the following steps:
[0109] (1) mixing HDI, polycaprolactone diol, polyethylene glycol and the first part of the catalyst and heating to 70° C. to react until the NCO content in the obtained mixture reaches the theoretical value, and cooling to room temperature;
[0110] (2) adding pentaerythritol tetrakis(3-mercaptopropionic acid), an inhibitor and a second part of the catalyst to the mixture, mixing and heating to 60° C. for reaction for 1 hour, then heating to 70° C. and adding pentaerythritol triallyl ether, 3-mercapto-1-propanol, a stabilizer and the remaining catalyst to mix and react until the NCO content in the mixture is 0%, thereby obtaining the thiol-modified polyurethane acrylate.
[0111] Specifically, the theoretical value may be 7.3%.
[0112] In some embodiments, the aliphatic difunctional polyurethane acrylate comprises the following raw materials in parts by weight:
[0113] IPDI 20-30 parts, polyether diol 130-170 parts, HEA 20-30 parts, inhibitor 0.01-1 part and catalyst 0.01-1 part;
[0114] The IPDI is produced by Wanhua Chemical Company (isophorone diisocyanate);
[0115] The molecular weight of the polyether diol 1 is 3000, HSH-230 produced by Jiangsu Haian Petrochemical Company; the molecular weight of the polyether diol 2 is 4000, HSH-240 produced by Jiangsu Haian Petrochemical Company; the molecular weight of the polyether diol 3 is 5000, HSH-250 produced by Jiangsu Haian Petrochemical Company;
[0116] The HEA is HEA (hydroxyethyl acrylate) produced by Fangda Chemical Company;
[0117] The inhibitor is methyl parahydroxyanisole (MEHQ) produced by Solvay Chemical Company;
[0118] The catalyst is dibutyltin dilaurate (DBT) produced by Shandong Yuanjin New Materials Co., Ltd.
[0119] In some embodiments, the method for preparing the aliphatic difunctional polyurethane acrylate comprises the following steps:
[0120] (1) mixing IPDI, polyether diol and the first part of the catalyst and heating to 80° C. under a protective atmosphere to react until the NCO content in the obtained mixture reaches the theoretical value, and then cooling to 40° C.;
[0121] (2) HEA and the remaining catalyst are added to the mixture and mixed, and then an inhibitor is added and the reaction is continued until the NCO content in the mixture is 0%, thereby obtaining the aliphatic difunctional polyurethane acrylate.
[0122] Specifically, the theoretical value may be 2.44%.
[0123] In some embodiments, the matte polyurethane acrylate is at least one of Baojun Chemical's 2022 product, Haohui New Materials' CR92209 product, and Wuxing Materials' LED9505 product.
[0124] In some embodiments, the matting powder is polydimethylsiloxane-modified fumed silica.
[0125] Furthermore, the matting agent is ACEMATT 3300 produced by Evonik Chemicals.
[0126] In some embodiments, the acrylate monomer is at least one of HEA and IBOA.
[0127] In some embodiments, the photoinitiator is a TPO initiator;
[0128] In some embodiments, the defoaming agent is a non-silicone defoaming agent;
[0129] Furthermore, the defoaming agent is TEGO920 produced by Digo;
[0130] In some embodiments, the dispersant is a modified siloxane dispersant;
[0131] Furthermore, the dispersant is at least one of TEGO 689, BYK 2008 and BYK 2009.
[0132] In some embodiments, the leveling agent is a polyacrylate leveling agent;
[0133] Furthermore, the leveling agent is BYK361N.
[0134] Examples 1 to 14
[0135] An embodiment of the frosted reinforcing adhesive of the present invention, the components of the frosted reinforcing adhesive are shown in Table 1, and the preparation method of the frosted reinforcing adhesive is as described above.
[0136] Wherein, the mercaptan-modified polyurethane acrylate 1 comprises the following raw materials in parts by weight:
[0137] 16.8 parts of HDI, 20.75 parts of polycaprolactone diol 1, 20 parts of polyethylene glycol 1, 48.9 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.5 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is as described above;
[0138] Thiol-modified polyurethane acrylate 2 comprises the following raw materials in parts by weight:
[0139] 16.8 parts of HDI, 16.6 parts of polycaprolactone diol 1, 24 parts of polyethylene glycol 1, 40.75 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 4.27 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is as described above;
[0140] Thiol-modified polyurethane acrylate 3 comprises the following raw materials in parts by weight:
[0141] 16.8 parts of HDI, 20.75 parts of polycaprolactone diol 1, 20 parts of polyethylene glycol 1, 32.6 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 8.53 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is as described above;
[0142] Thiol-modified polyurethane acrylate 4 comprises the following raw materials in parts by weight:
[0143] 16.8 parts of HDI, 20.75 parts of polycaprolactone diol 1, 20 parts of polyethylene glycol 1, 61.13 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.5 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is as described above;
[0144] Thiol-modified polyurethane acrylate 5 comprises the following raw materials in parts by weight:
[0145] 16.8 parts of HDI, 10 parts of polycaprolactone diol 2, 20 parts of polyethylene glycol 1 (molecular weight 800), 48.9 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.5 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is as above and step (1) is reacted until the NCO content in the obtained mixture reaches the corresponding theoretical value of 8.97%;
[0146] Thiol-modified polyurethane acrylate 6 comprises the following raw materials in parts by weight:
[0147] 16.8 parts of HDI, 37.5 parts of polycaprolactone diol 3, 20 parts of polyethylene glycol 1, 48.9 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.5 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is as described above and step (1) is reacted until the NCO content in the obtained mixture reaches the corresponding theoretical value of 5.65%;
[0148] Thiol-modified polyurethane acrylate 7 comprises the following raw materials in parts by weight:
[0149] 16.8 parts of HDI, 20.75 parts of polycaprolactone diol 1, 5 parts of polyethylene glycol 2, 48.9 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.5 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is as described above and step (1) is reacted until the NCO content in the obtained mixture reaches the corresponding theoretical value of 9.87%;
[0150] Thiol-modified polyurethane acrylate 8 comprises the following raw materials in parts by weight:
[0151] 16.8 parts of HDI, 20.75 parts of polycaprolactone diol 1, 50 parts of polyethylene glycol 3, 48.9 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.5 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is as described above and step (1) is reacted until the NCO content in the obtained mixture reaches the corresponding theoretical value of 4.80%;
[0152] The aliphatic difunctional polyurethane acrylate 1 comprises the following raw materials in parts by weight:
[0153] 22.2 parts of IPDI, 1150 parts of polyether diol, 23.2 parts of HEA, 0.1 parts of inhibitor and 0.1 parts of catalyst; the preparation method is as described above;
[0154] The aliphatic difunctional polyurethane acrylate 2 comprises the following raw materials in parts by weight:
[0155] 22.2 parts of IPDI, 275 parts of polyether diol, 23.2 parts of HEA, 0.1 parts of inhibitor and 0.1 parts of catalyst; the preparation method is as above and step (1) is reacted until the NCO content in the obtained mixture reaches 4.32%;
[0156] The aliphatic difunctional polyurethane acrylate 3 comprises the following raw materials in parts by weight:
[0157] 22.2 parts of IPDI, 250 parts of polyether diol 3, 23.2 parts of HEA, 0.1 parts of inhibitor and 0.1 parts of catalyst; the preparation method is as above and step (1) is reacted until the NCO content in the obtained mixture reaches 1.54%;
[0158] The matte polyurethane acrylate 1 is Haohui New Material CR92209;
[0159] The matte polyurethane acrylate 2 is Baojun Chemical 2022;
[0160] The matte polyurethane acrylate 3 is five-element material LED 9505;
[0161] The acrylate monomer 1 is HEA;
[0162] The acrylate monomer 2 is IBOA;
[0163] Table 1
[0164]
[0165]
[0166] Comparative Examples 1 to 12
[0167] A frosted reinforcing adhesive, the components of which are shown in Table 2, and the only difference from the embodiment is the components.
[0168] Wherein, the commercially available UV resin 1 is BW L899 produced by Bahe New Materials Company;
[0169] The commercially available UV resin 2 is BW L847 produced by Bahe New Materials Company;
[0170] The commercially available UV resin 3 is 2011 produced by Baojun Chemical Company;
[0171] The thiol-modified polyurethane acrylate 9 comprises the following raw materials in parts by weight:
[0172] 16.8 parts of HDI, 20.75 parts of polycaprolactone diol 1, 20 parts of polypropylene glycol (molecular weight 800, PPG-800 produced by Jiangsu Hai'an Petrochemical Company), 48.9 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.5 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is:
[0173] (1) placing polycaprolactone diol and polypropylene glycol in a four-necked flask equipped with a stirrer, a thermometer and a reflux condenser, heating to 120° C. for dehydration for 30 min, and then cooling to room temperature to obtain component A;
[0174] (2) adding HDI and dibutyltin dilaurate to component A, heating to 80° C. to react until the NC content reaches 7.30%, and cooling to obtain component B;
[0175] (3) adding a solvent to component B, and then adding pentaerythritol diacrylate, 3-mercapto-1-propanol, and a polymerization inhibitor and mixing them evenly, and heating to 60° C. under nitrogen protection to react for 24 hours until the NCO content value is 0, and finally adding the remaining stabilizer and polymerization inhibitor and stirring and mixing evenly to obtain the thiol-modified polyurethane acrylic UV resin;
[0176] The thiol-modified polyurethane acrylate 10 comprises the following raw materials in parts by weight:
[0177] 16.8 parts of HDI, 20.75 parts of polycaprolactone triol (molecular weight 830, produced by Juren Chemical 3087), 20 parts of polyethylene glycol 1, 48.9 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0.5 parts of pentaerythritol triallyl ether, 0.5 parts of 3-mercapto-1-propanol, 0.1 parts of inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst; the preparation method is:
[0178] (1) mixing HDI, polycaprolactone triol, polyethylene glycol and the first part of the catalyst and heating to 70° C. to react until the NCO content in the obtained mixture reaches a theoretical value of 10.49%, and then cooling to room temperature;
[0179] (2) adding pentaerythritol tetrakis(3-mercaptopropionic acid), a polymerization inhibitor and a second part of the catalyst to the mixture, mixing and heating to 60° C. for reaction for 1 hour, then heating to 70° C. and adding pentaerythritol triallyl ether, 3-mercapto-1-propanol, a stabilizer and the remaining catalyst to mix and react until the NCO content in the mixture is 0%, thereby obtaining the thiol-modified polyurethane acrylate;
[0180] The mercaptan-modified polyurethane acrylate 11 is commercially available mercaptan-modified polyurethane acrylate FSP8630 produced by Runao Chemical Company;
[0181] The polyurethane acrylate comprises the following raw materials in parts by weight: 16.8 parts of HDI, 20.75 parts of polycaprolactone diol 1, 20 parts of polyethylene glycol 1, 25.6 parts of pentaerythritol triallyl ether, 0.1 parts of polymerization inhibitor, 0.3 parts of stabilizer and 0.1 parts of catalyst;
[0182] The preparation method is:
[0183] (1) mixing HDI, polycaprolactone diol, polyethylene glycol and the first part of the catalyst and heating to 70° C. to react until the NCO content of the obtained mixture reaches 7.30%, and then cooling to room temperature;
[0184] (2) adding pentaerythritol triallyl ether, a stabilizer and the remaining catalyst to the mixture, mixing and heating to 70-75° C., and reacting until the NCO content in the mixture is 0%, thereby obtaining the polyurethane acrylate;
[0185] The aliphatic difunctional polyurethane acrylate 4 comprises the following raw materials in parts by weight:
[0186] 22.2 parts of IPDI, 30 parts of polyether diol 4, 23.2 parts of HEA, 0.1 parts of inhibitor and 0.1 parts of catalyst; the molecular weight of the polyether diol 4 is 600, HSH-206 produced by Jiangsu Haian Petrochemical Company; the preparation method is the same as the preparation method of aliphatic difunctional polyurethane acrylate 1-3, and step (1) is reacted until the NCO content in the obtained mixture reaches the corresponding theoretical value of 8.05%;
[0187] The aliphatic difunctional polyurethane acrylate 5 comprises the following raw materials in parts by weight:
[0188] 22.2 parts of IPDI, 150 parts of polybutylene adipate (PBA) (molecular weight 3000, HY-3022 produced by Xuzhou Yihuiyang Company), 23.2 parts of HEA, 0.1 parts of inhibitor and 0.1 parts of catalyst; the preparation method is the same as the preparation method of aliphatic difunctional polyurethane acrylate 1 to 3, and step (1) is reacted until the NCO content in the obtained mixture reaches the corresponding theoretical value of 2.44%;
[0189] The aliphatic difunctional polyurethane acrylate 6 comprises the following raw materials in parts by weight:
[0190] 22.2 parts of IPDI, 150 parts of polycarbonate diol (PCDL) (molecular weight 3000, PCDL-300 produced by Hubei Yamade Co., Ltd.), 23.2 parts of HEA, 0.1 parts of inhibitor and 0.1 parts of catalyst; the preparation method is the same as the preparation method of aliphatic difunctional polyurethane acrylate 1 to 3, but in step (1), the reaction is carried out until the NCO content in the obtained mixture reaches the corresponding theoretical value of 2.44%.
[0191] The product components, raw materials, preparation processes, etc. described in each comparative example are the same as those in the embodiments unless otherwise specified.
[0192] Table 2
[0193]
[0194]
[0195] Effect Example 1
[0196] In order to verify the use effect of the products described in the present invention, each product was tested as follows:
[0197] (1) Viscosity test: tested according to GB / T 7193-2008, temperature is 25°C, unit is cps;
[0198] (2) Shore hardness test: Tested in accordance with GB / T 2411-2008;
[0199] (3) Glossiness test: Tested according to GB / T 9754-2007 (60°). According to commercialization requirements, the glossiness of the product needs to be maintained at 15-35° to maintain matte properties and avoid covering up the pattern when used for nail art;
[0200] (4) Quick-drying test: The products prepared in the embodiments and comparative examples were applied to commercially available black nail tips with a thickness of 30 to 40 μm. The applied nail tips were placed in a commercially available nail lamp (48 lamp beads, total power 48 W), and the irradiation switch was turned on. The nail tips were taken out every 5 seconds to check whether the surface was completely dry. The observation time was recorded. The recorded time was the drying time. The faster the drying, the shorter the drying time. Commercial products were required to be surface dry within 30 seconds (including 30 seconds).
[0201] (5) Anti-powder sticking effect: Take the 3683 series color glue sold by Meisi Company and apply it on the light-colored nail plate according to the process requirements and cure it. Then brush the products of each embodiment and comparative example with a brushing thickness of 30-40um. After curing, use a painting line brush to apply the 2071 sticky powder glue sold by Meisi Company with a brushing amount of 100um. After curing, apply TWB 6683 magic mirror powder produced by Dongguan Taiheng Pigment Company until it is evenly applied. Then use a brush to remove the excess magic mirror powder. Observe whether there is any magic mirror powder residue in the area on the surface of the product without sticky powder glue. The specific process is as follows: Figures 1-2 As shown;
[0202] (6) Adhesion test: 3683 series color glue sold by Meisi Company was applied on light-colored nail pieces and cured according to the process. Then, the products of each embodiment and comparative example were applied with a brushing amount of 30-40 μm. After curing, 2072 adhesive powder glue sold by Meisi Company was applied with a painting line pen with a brushing amount of 100 μm. After curing, a mechanical force arm was used to pull from one corner of the cured product with a force of 3N to observe whether the cured adhesive powder glue would fall off;
[0203] (7) Flexibility test: Take the 3683 series color glue sold by Meisi Company and brush it on the light-colored nail plate according to the process requirements and cure it. Then brush the products of each embodiment and comparative example with a brushing thickness of 30-40 um. After curing, fold the nail plate 180° to observe whether the glue film is cracked. If there is no crack, reset the nail plate and record it as 1 time. If there is cracking, record it as less than 1 time, repeat the folding operation. If there is no cracking, record the result as 2 times. Repeat the test and record the results.
[0204] (8) Heat release test: The reinforcing glue prepared in each embodiment and comparative example was brushed on a real human nail with a thickness of 30-40 μm. The finger was placed under a nail lamp (48 lamp beads, total power 48 W) for curing. The heat release during curing was felt by the finger. The greater the heat release, the more obvious the burning pain of the finger. There are four main index levels: slightly hot means that the heat can be felt but not hot (no pain); slightly hot means that a little hot can be felt (the finger has a slight pain); hot means that the finger clearly feels hot (there is obvious pain, but it can still be tolerated); very hot means unbearable pain;
[0205] (9) Recoatability test: The reinforcing glue prepared in each embodiment and comparative example is brushed on the black nail plate with a brushing thickness of 30 to 40 μm. After curing according to the process requirements, the sealing glue 3109 sold by Meisi Company is brushed on the glue layer with a brushing thickness of about 20 μm. After brushing, observe whether the sealing glue shrinks. After curing according to the process requirements, if shrinkage occurs or the coating falls off, it means that the recoatability is poor and is recorded as N. If no shrinkage occurs, it is recorded as OK.
[0206] The test results are shown in Tables 3 and 4. In order to verify the preference of the product of the present invention, the 3109 product produced by Meisi Company, which is used as a sealing glue in the existing nail art process, was used as a control product to carry out the same test.
[0207] Table 3
[0208]
[0209]
[0210] Table 4
[0211]
[0212] It can be clearly seen from the test results that the frosted reinforcement glue of the present invention has a good use experience and effect. When in use, the viscosity is relatively high, which can reach more than 2400cps, and the hardness also reaches 45D and above. It has good wear resistance and high flexibility. It can be folded in half 3 times without cracking at best, and the glossiness is maintained within 40°. It has an ideal matte appearance, and can achieve the effect of no powder sticking or slight powder sticking in the powder sticking test. It is not easy to fall off after attaching the nail plate, and can be re-coated without shrinking or falling off. In terms of use experience, the product only takes a maximum of 30 seconds to cure, which meets the requirements of commercial use, and the experiencer will not feel unbearable heat during curing, and some products can even achieve a slight degree of heat, with a better use experience. The product of the present invention is used as a reinforcement glue. After the nail plate has gone through the steps of gluing, setting the reinforcement glue, bonding the magic mirror powder, and encapsulating the coating, the obtained nail plate has high aesthetics and a long service life. Figure 3shown.
[0213] It can be seen from Example 1 and Examples 6 to 8 that the comprehensive performance of products prepared by polyurethane acrylates with different thiol modification degrees is also different. In addition to the basic properties of the product, which are directly reflected in the viscosity and hardness of the product, the adhesion, flexibility, quick-drying and heat release of the product are also different. Among them, too high or too low a modification degree will lead to an increase in product heat and a decrease in flexibility. The comprehensive performance of the products in Example 1 and Example 6 with a relatively moderate degree of modification is better. However, in general, these products are better than existing products and products prepared by conventional UV resin compounding. The existing reference product cannot achieve the non-stick powder effect, and has poor adhesion and too high gloss, and cannot achieve a matte effect. When used for nail art later, it will directly cover the pattern. The quick-drying property of the comparative example 1 product is too poor, and it is also impossible to achieve a non-stick powder effect. In addition, the product feels too hot and has a poor user experience.
[0214] It can be seen from Examples 1 and 9 to 12 that in the process of synthesizing thiol-modified polyurethane acrylate, the molecular weights of polycaprolactone diol and polyethylene glycol will also affect the performance of the product. When polycaprolactone diol with a molecular weight of 800 to 900 and polyethylene glycol with a molecular weight of 750 to 850 are used, the corresponding frosted reinforcing adhesive has better comprehensive performance. However, in comparison, these products are better than the products prepared in Comparative Examples 6 to 8. During the synthesis process of these products, the thiol-modified polyurethane acrylate is not obtained by the reaction of polycaprolactone diol and polyethylene glycol. The reaction system of the thiol-modified polyurethane acrylate in the product of Comparative Example 6 is a polycaprolactone diol and polypropylene glycol system, the system of polycaprolactone ternary village and polyethylene glycol in the product of Comparative Example 7, and the product of Comparative Example 8 is an existing commercially available product. These products cannot be well compounded with aliphatic difunctional polyurethane acrylate. Therefore, the products not only cannot achieve matte gloss, but also cannot take into account the comprehensive effects of non-stick powder, strong adhesion, flexibility and recoatability. Some performances are even worse than those of the product of Comparative Example 9 prepared from polyurethane acrylate that has not been modified by thiol. The performance of the product is weakened after inappropriate thiol modification.
[0215] According to Example 1, Example 13-14 and Comparative Examples 2-3, Comparative Examples 10-12, it can be seen that compared with conventional UV resin compounded thiol-modified polyurethane acrylate, only the aliphatic difunctional polyurethane acrylate in the product of the present invention can be compounded to achieve the comprehensive characteristics of non-sticky powder, strong adhesion, and good recoatability, and during preparation, the selected raw material system must be a high molecular weight polyether diol reaction system. If the molecular weight of the selected polyether diol is too low, or other types of reaction systems are selected, the product performance cannot reach the current use effect. However, as the molecular weight of the polyether diol increases, the viscosity of the product will also increase, the stability will decrease, the stickiness will increase and the flexibility will decrease. Therefore, the aliphatic difunctional polyurethane acrylate prepared by the polyether diol system with a molecular weight of 3000-3500 is more effective.
[0216] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essential scope of the technical solution of the present invention.
Claims
1. A frosted reinforcement adhesive, characterized in that: The composition comprises the following components in parts by weight: 10-40 parts of mercaptan-modified polyurethane acrylate, 20-40 parts of aliphatic difunctional polyurethane acrylate; The thiol-modified polyurethane acrylate comprises the following preparation raw materials: HDI, polycaprolactone diol, polyethylene glycol, pentaerythritol tetrakis(3-mercaptopropionic acid) ester, pentaerythritol triallyl ether, and 3-mercapto-1-propanol; The aliphatic difunctional polyurethane acrylate comprises the following preparation raw materials: IPDI, polyether diol, HEA; the molecular weight of the polyether diol is ≥3000.
2. The frosted reinforcement adhesive as claimed in claim 1, characterized in that: The frosted reinforcing adhesive also includes 10 to 20 parts of matte polyurethane acrylate and 2 to 10 parts of matte powder.
3. The frosted reinforcement adhesive as claimed in claim 1, characterized in that: The frosted reinforcing adhesive comprises the following components in parts by weight: 30-40 parts of thiol-modified polyurethane acrylate and 20-30 parts of aliphatic difunctional polyurethane acrylate.
4. The frosted reinforcement adhesive as claimed in claim 1, characterized in that: In the raw materials for preparing the mercaptan-modified polyurethane acrylate, the molecular weight of the polycaprolactone diol is 300-1800.
5. The frosted reinforcement adhesive as claimed in claim 1, characterized in that: In the raw materials for preparing the mercaptan-modified polyurethane acrylate, the molecular weight of polyethylene glycol is 100-2200.
6. The frosted reinforcement adhesive as claimed in claim 1, characterized in that: The thiol-modified polyurethane acrylate comprises the following raw materials in parts by weight: 15-20 parts of HDI, 10-40 parts of polycaprolactone diol, 5-50 parts of polyethylene glycol, 32-49 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0-15 parts of pentaerythritol triallyl ether, 0.1-1 parts of 3-mercapto-1-propanol, 0.01-0.5 parts of inhibitor, 0.01-0.5 parts of stabilizer and 0.01-0.5 parts of catalyst.
7. The frosted reinforcing adhesive as claimed in claim 6, characterized in that: The thiol-modified polyurethane acrylate comprises the following raw materials in parts by weight: 16-17 parts of HDI, 16-21 parts of polycaprolactone diol, 20-24 parts of polyethylene glycol, 40-49 parts of pentaerythritol tetrakis(3-mercaptopropionic acid), 0-9 parts of pentaerythritol triallyl ether, 0.4-0.6 parts of 3-mercapto-1-propanol, 0.08-0.12 parts of polymerization inhibitor, 0.2-0.3 parts of stabilizer and 0.2-0.4 parts of catalyst.
8. The frosted reinforcing adhesive as claimed in claim 6, characterized in that: The preparation method of the thiol-modified polyurethane acrylate comprises the following steps: (1) mixing HDI, polycaprolactone diol, polyethylene glycol and the first part of the catalyst and heating to 65-75° C. to react until the NCO content in the obtained mixture reaches the theoretical value, and cooling to room temperature; (2) adding pentaerythritol tetrakis(3-mercaptopropionic acid), an inhibitor and a second part of the catalyst to the mixture, mixing and heating to 58-62° C. for reaction for 0.8-1.2 hours, then heating to 68-72° C. and adding pentaerythritol triallyl ether, 3-mercapto-1-propanol, a stabilizer and the remaining catalyst to mix and react until the NCO content in the mixture is 0%, thereby obtaining the thiol-modified polyurethane acrylate.
9. The frosted reinforcement adhesive as claimed in claim 1, characterized in that: In the raw materials for preparing the aliphatic difunctional polyurethane acrylate, the molecular weight of the polyether diol is 3000-5000.
10. The frosted reinforcement adhesive as claimed in claim 1, characterized in that: The aliphatic difunctional polyurethane acrylate comprises the following raw materials in parts by weight: 20-30 parts of IPDI, 130-170 parts of polyether diol, 20-30 parts of HEA, 0.01-1 part of polymerization inhibitor and 0.01-1 part of catalyst.
11. The frosted reinforcement adhesive as claimed in claim 10, characterized in that: The aliphatic difunctional polyurethane acrylate comprises the following raw materials in parts by weight: IPDI 22-23 parts, polyether diol 145-155 parts, HEA 22-25 parts, polymerization inhibitor 0.08-0.12 parts and catalyst 0.1-0.3 parts.
12. The frosted reinforcing adhesive as claimed in claim 10, characterized in that: The preparation method of the aliphatic difunctional polyurethane acrylate comprises the following steps: (1) mixing IPDI, polyether diol and the first part of the catalyst and heating to 75-85° C. under a protective atmosphere to react until the NCO content in the obtained mixture reaches the theoretical value, and then cooling to 35-45° C.; (2) HEA and the remaining catalyst are added to the mixture and mixed, and then an inhibitor is added and the reaction is continued until the NCO content in the mixture is 0%, thereby obtaining the aliphatic difunctional polyurethane acrylate.
13. The frosted reinforcement adhesive as claimed in claim 1, characterized in that: The frosted reinforcing adhesive also includes 5 to 20 parts of acrylate monomer.
14. The frosted reinforcement adhesive as claimed in claim 13, characterized in that: The acrylic acid ester monomer is at least one of hydroxyethyl acrylate, isobornyl acrylate and methacrylate.
15. The frosted reinforcing adhesive as claimed in claim 1, characterized in that: The components of the frosted reinforcement glue also include 1 to 6 parts of photoinitiator, 0.1 to 1 part of defoamer, 0.1 to 1 part of dispersant and 0.1 to 1 part of leveling agent.
16. The method for preparing the frosted reinforcing adhesive according to any one of claims 1 to 15, characterized in that: The following steps are involved: (1) mixing thiol-modified polyurethane acrylate, aliphatic difunctional polyurethane acrylate, matte polyurethane acrylate, acrylate monomer and photoinitiator until uniform to obtain a mixture A; (2) adding matting powder, defoaming agent, dispersant and leveling agent to mixture A and continuing to mix until uniform, to obtain mixture B; (3) The mixture is passed through a 100-200 mesh sieve to obtain the frosted reinforcing adhesive.
17. The method for preparing the frosted reinforcing adhesive as claimed in claim 16, characterized in that: The mixing rate in step (1) is 750-1000 rpm, and the mixing time is 10-15 min.
18. The method for preparing the frosted reinforcing adhesive as claimed in claim 16, characterized in that: The mixing rate in step (2) is 1200-1500 rpm, and the mixing time is 20-30 min.
19. Use of the frosted reinforcing adhesive as claimed in any one of claims 1 to 15 as an isolation layer in nail art.
20. A manicure, characterized in that: It comprises the frosted reinforcement adhesive as described in any one of claims 1 to 15.